Tumor‐associated macrophages: potential role in skeletal involvement in classic Hodgkin lymphoma - Maja Dam Andersen; Katharina Wolter; Marie Hairing Enemark; Mette Abildgaard Pedersen; Lars Christian Gormsen; Kristina Lystlund Lauridsen; Jørn Starklint; Stephen Jacques Hamilton‐Dutoit; Francesco d'Amore; Maja Ludvigsen; Peter Kamper (The Journal of Pathology: Clinical Research)
Abstract The biology of tumor spread to bone is poorly understood, not least in classic Hodgkin lymphoma (cHL). We used gene expression profiling and immunohistochemistry to characterize the nodal tumor microenvironment of cHL cases with and without skeletal involvement at diagnosis. Gene expression profiling of 66 pretreatment lymphoma samples revealed that lymph nodes from patients with skeletal cHL (s‐cHL) exhibited a higher abundance of cells expressing macrophage markers, particularly M2‐like markers, than nodal‐only cHL (n‐cHL). These markers included CD163, MRC1 (CD206), MARCO, and SIGLEC1. Additionally, there was a notable downregulation of genes encoding B‐cell‐associated markers such as MS4A1 (CD20), CD19, PAX5, and CD79A/B. We further evaluated the protein expression of macrophage markers (CD68, CD163, and CD206) and the B‐cell marker CD20 in 193 pretreatment lymphoma samples using immunohistochemistry. Our analysis revealed significantly higher expression levels of all three macrophage markers in s‐cHL samples compared to n‐cHL samples (p < 0.001). Conversely, the expression level of CD20 was significantly lower in s‐cHL compared with n‐cHL (p < 0.001). All three macrophage markers correlated positively with Ann Arbor stage, indicating their potential involvement in the dissemination of cHL in general. Our findings suggest a potential role for tumor‐associated macrophages in the dissemination of cHL to bone.